2018
DOI: 10.1111/ics.12466
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic regulation of human skin melanogenesis and pigmentation

Abstract: In human skin, melanogenesis is a tightly regulated process. Indeed, several extracellular signals are transduced via dedicated signalling pathways and mostly converge to MITF, a transcription factor integrating upstream signalling and regulating downstream genes involved in the various inherent mechanisms modulating melanogenesis. The synthesis of melanin pigments occurs in melanocytes inside melanosomes where melanogenic enzymes (tyrosinase and related proteins) are addressed with the help of specific protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
187
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(210 citation statements)
references
References 176 publications
1
187
0
7
Order By: Relevance
“…Tyrosinase is an enzyme that serves a key role in melanin pigment production [ 25 ]. When melanin is synthesized, it not only promotes aging of the skin, but also causes skin hyperpigmentation and dark spots.…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosinase is an enzyme that serves a key role in melanin pigment production [ 25 ]. When melanin is synthesized, it not only promotes aging of the skin, but also causes skin hyperpigmentation and dark spots.…”
Section: Resultsmentioning
confidence: 99%
“…1 The ratio of liposome composition is molar ratio. 2 The ratio of liposome composition is weight ratio highest EE (93.55%). Amnuaikit et al [12] reported that conventional liposome showed vesicle size, zeta potential and entrapment efficiency of 641.52±19.02 nm, -27.32±1.00 and 53.55±4.9%, respectively.…”
Section: Liposome Formulation and Characterizationmentioning
confidence: 99%
“…Skin pigmentation is a physiological defense against ultraviolet radiation (UVR) and it results in the production and distribution of melanin in epidermis [1,2]. UVR which has specific wavelengths can be divided into 3 types including UVA, UVB and UVC [3].…”
Section: Introductionmentioning
confidence: 99%
“…In normal aging, the beginning of hair graying occurs at the age of 34 ± 9.6, 43.9 ± 10.3, and 39 ± 9 in Caucasians, African Americans, and Asians, respectively. The melanocyte stem cells responsible for the production of key pigment melanin decrease with age, and this loss of melanocyte stem cells has been explained in various studies …”
Section: Review Of Literaturementioning
confidence: 99%